Understanding the effects of nutrition and mental health conditions for patients with opioid use disorder (OUD) - Thiesset, Heather F; Barber, Melinda; Hall, Sarah M; Johnson, Emma; McBride, Elaine; Larsen, Merilee (Journal of opioid management, 2024)
The ravaging effects of the opioid epidemic have affected our communities locally and nationally and are multifaceted in their cause and treatment. It is imperative to locate multiple modalities of treatment options and care for patients with opioid use disorder (OUD) including developing healthy nutrition habits and addressing mental health concerns. Understanding patient perceptions of their personal nutrition habits and mental health status is imperative to providing holistic care in the OUD patient population. An anonymous 31-question Likert-scale and multiple-choice survey was administered to patients with an International Classification of Disease (ICD-10) code in their electronic medical record of OUD (N = 124). χ and Fisher's exact test where appropriate were performed to determine the demographics of survey participants who acknowledged history of OUD compared to those who did not acknowledge a history of OUD. Log-binomial models were used to generate adjusted prevalence ratios. Of the 117 patients identified using ICD-10 codes from their medical records as having OUD, only 63 patients acknowledged having a history of OUD, while 54 patients did not. A univariate analysis showed differences in marital status for patients with a self-identified history of OUD. They were also more likely to not be married (divorced or single) (p < 0.01). Patients also tended to be younger than 50 years of age (p < 0.01) and non-White (p < 0.01). There were no differences seen for patients with a history of OUD in the categories of employment (p = 0.31) status or sex (p = 0.51). Patients who acknowledged a history of OUD were significantly more likely to understand the relationship between a healthy diet and reducing the intensity of opioid cravings (p = 0.01) and more likely to consider using nutrition to help combat opioid cravings (p = 0.01). There were no significant differences in overall health or the use of supplements as a part of opioid use treatment. Significant differences were found between those acknowledging a history of OUD having higher rates of depression (p = 0.02) and anxiety (p = 0.02) treatment, despite there not being differences in condition rates for these two conditions (depression, p = 0.08; anxiety, p = 0.27) between the groups. Patients with patient-confirmed OUD were more likely to receive medication treatment (p = 0.03) than those without this acknowledgment. A similar disease burden of anxiety and depression existed for patients acknowledging OUD as opposed to patients denying OUD. However, significant differences existed between these groups in medication treatment, with those acknowledging OUD having higher rates of being treated for both depression and anxiety. Understanding a patient's mental health condition(s) can be impactful for the treatment of OUD. Multifaceted treatment options should include addressing nutritional deficiencies that impact cravings and long-term healing for patients. Nutrition and mental health are key parts of a multifaceted treatment modality for patients dealing with OUD. Assisting patients in treatment for depression and anxiety as well as nutrition can change the trajectory of a patient's opioid use recovery.